The Concept of Coherence in Art - Aschenbrenner, L. author. aut Link
256 p.
Keywords: This book concerns a single topic, coherence in the several arts, which is vague to begin with, but becomes progressively more precise as we proceed. While the book is not a formalist theory of art it aims to take steps toward clearing up the concept of form, which is of central interest in art, either by its observance or by deliberate defiance. While our interest is thus in one concept, it is as a matter of fact complex and covers some seven subordinate topics. Each of these important subjects is covered in separate chapters: the number of principal parts of artworks, their extent, size or magnitude, the intervallic relation between them, and their dimensional, contextual, tendentive, and connotational relations, all of which will be explained as we proceed. There are ample analyses or critiques devoted to particular artworks which appear in Part Two. While the book keeps to a fairly narrow range of subjects, breadth is there too, and the implication for all the arts is manifest. The examples cover mainly music, but there is a broad selection of architecture, sculpture, painting, both abstract and figural, and a brief selection from the field of narrative poetic art. Many more types of the arts had to be excluded to make the book of manageable size.